Construction of a mathematical model and numerical study of interaction between moisture-, heat-, and mass transfer processes of salt solutions in an unsaturated soil layer - Ilkiv, Ihor; Zhukovskyy, Viktor; Zhukovska, Nataliia; Safonyk, Andrii (Eastern-European Journal of Enterprise Technologies, 2022)
Methods of mathematical modeling and computer simulation were used to investigate the influence of interrelated processes of transfer of saline solutions in the unsaturated soil layer. To this end, a mathematical model has been built for modeling the corresponding processes of the moisture-, heat-, and mass transfer of saline solutions in an unsaturated soil layer. An effective computational algorithm was developed to solve the corresponding nonlinear boundary problem numerically by the method of finite differences; it was implemented in the Asp.net programming environment in the C++ language. Based on the numerical experiments carried out, the distribution of moisture, concentration, and temperature fields in the aeration zone (incomplete saturation) was obtained. To study the influence of mass transfer of salts on moisture transfer, a numerical solution was found to the problem of moisture transfer, the problem of moisture transfer taking into consideration mass transfer and moisture transfer, taking into consideration mass transfer in the presence of osmosis. Analysis of the results showed that the distribution of the concentration of saline solutions over time is slower and more predictable. It was established that the distribution of moisture heads increases with depth and time when saline solutions fall on the surface of the soil massif. With the influence of salt concentration, the distribution of moisture increases with depth and time throughout the entire area of moisture transfer by 1–3 %. The distribution of moisture heads taking into consideration the concentration of salts and osmosis is reduced by 3–5 % compared to the results of the problem without taking into consideration the phenomenon of osmosis. The distribution of the concentration of saline solutions during moisture transfer and osmosis acquires higher values compared to the results without taking osmosis into consideration. The established features can be successfully applied to clean the fertile soil layer and resume agricultural activities